$L^{∞}$ Convergence of Conforming Finite Elements for the Biharmonic Equation (Journal of Computational Mathematics, 2021)
The paper considers the $L^{∞}$ convergence for conforming finite elements, such as Argyris element, Bell element and Bogner-Fox-Schmit element, solving the boundary value problem of the biharmonic equation. The nearly optimal order $L^{∞}$ estimates are given.